In-hospital growth and long-term neurodevelopmental outcomes of very low birth weight infants - Consales, Alessandra; Porro, Matteo; Gangi, Silvana; Pesenti, Nicola; Gardon, Laura; Squarza, Chiara; Frigerio, Andrea; Lezzi, Irene; Vizzari, Giulia; Morniroli, Daniela; Macchi, Marta; Fontana, Camilla; et al. (Frontiers in Pediatrics, 2023)
Background and Objectives: Very low birth weight infants (VLBW) are at risk for adverse growth and neurodevelopmental outcomes. We aimed to evaluate the association between growth during Neonatal Intensive Care Unit (NICU) stay and long-term neurodevelopmental outcomes in a cohort of preterm VLBW newborns. Methods: We conducted a longitudinal observational study in the Follow-up Service of our Clinic from January 2014 to April 2017. All preterm VLBW infants born at our hospital and enrolled in our follow-up program were considered eligible for the study. The neurodevelopmental assessment was performed using the Griffiths Mental Development Scales at 12 and 24 months corrected age. Results: Study population included 172 subjects (47.1% males) with a mean gestational age of 29 weeks and a mean birth weight of 1117g. A unitarian Δz-score increase in head circumference from birth to discharge was associated with a 1.6-point increase in General Quotient at 24 months corrected age. An association with subscales C and D was also found. Likewise, an increase in length Δz-score was associated with better 24-month subscale C scores although not reaching statistical significance. No relationship with the outcome at 24 months was found for weight gain. Conclusions: Growth during NICU stay appears to be related to a more favorable neurodevelopmental outcome at 24 months corrected age, especially in the hearing and language domain (subscale C). The longitudinal evaluation of auxological parameters during hospitalization can contribute to the identification of subjects at risk for adverse neurodevelopmental outcomes in the first years of life.